Microbiological contamination and mycotoxin detection in guarana integument: addressing safety concerns in guarana agro-industrial co-products - Lima, Clara Mariana Gonçalves; Amorim-Neto, Dionísio Pedro; Neuenfeldt, Naiara Hennig; Giordano, Ana Luísa Perini Leme; Schreiber, Angélica Zaninelli; Rocha, Liliana de Oliveira; Sant’Ana, Anderson de Souza; Efraim, Priscilla; Ramos, Simone de Nazaré Melo (Food Science and Technology, 2025)
This study characterized the microbiota of guarana integument, a co-product of guarana production chain, and validated an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method for mycotoxin detection. Despite its low water activity, guarana integument harbors diverse microorganisms, including pathogens (Bacillus cereus), enteric opportunists (Enterococcus casseliflavus, Citrobacter freundii, Kosakonia radicincitans, Enterobacter cloacae, and Enterobacter bugandensis), and spoilage organisms (molds, yeasts, and spore-forming bacteria). Mold and yeast counts above the quantification limit were found only in samples from Producers 1 and 3 (3.00 and 4.35 log₁₀ colony-forming unit [CFU]/g, respectively). Aerobic mesophilic bacteria were present in all samples (2.65–4.27 log₁₀ CFU/g), while Enterobacteriaceae contamination was detected only in Producer 3 (1.77 log₁₀ CFU/g). B. cereus vegetative cells were found in Producers 1 and 3 (2.85 and 2.30 log₁₀ CFU/g), raising safety concerns. No Salmonella sp. or Listeria monocytogenes were detected. Aerobic mesophilic spore-forming bacteria were present in all samples, with Producer 3 showing the highest count (> 6 log₁₀ spores/g) and being the only thermophilic spores above the limit (2.17 log₁₀ spores/g). Aflatoxins B1 and B2, and ochratoxin A were below detection limits. These findings highlight potential risks to casquilho’s microbiological stability.